2021
DOI: 10.1007/s00723-020-01304-z
|View full text |Cite
|
Sign up to set email alerts
|

EPR Everywhere

Abstract: This review is inspired by the contributions from the University of Denver group to low-field EPR, in honor of Professor Gareth Eaton's 80th birthday. The goal is to capture the spirit of innovation behind the body of work, especially as it pertains to development of new EPR techniques. The spirit of the DU EPR laboratory is one that never sought to limit what an EPR experiment could be, or how it could be applied. The most well-known example of this is the development and recent commercialization of rapid-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 167 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…Recently, small and mobile EPR scanners have indeed been suggested that combine portability with the superior detection sensitivity that is known from lab-based EPR instruments as a consequence of the larger electron magnetic moment [13,14]. See [15] for an overview of recent low-field and portable EPR applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, small and mobile EPR scanners have indeed been suggested that combine portability with the superior detection sensitivity that is known from lab-based EPR instruments as a consequence of the larger electron magnetic moment [13,14]. See [15] for an overview of recent low-field and portable EPR applications.…”
Section: Introductionmentioning
confidence: 99%
“…S INCE the discovery of Electron Spin Resonance (ESR) by Zavoisky in 1944 at Kazan University [1], there has been vast development in the field of magnetic resonance. Nowadays, ESR methodologies cover various science disciplines [2], including solid-state physics [3]- [7], quantum information processing [8], [9], biophysics [10]- [14], and chemistry [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…ESR has broad applications ranging from physics, over chemistry to biology, and therefore a wide variety of samples types exist with different requirements [2], [48]. The message of this article is to show that any spectrometer using a sample holder without a resonator (non-resonant sample holder) has a wide range of applications, which can be reached by designing new sample holders.…”
Section: Introductionmentioning
confidence: 99%
“…The results can be explained by the EPR signal arises from the electron Zeeman interaction and the hyperfine interaction then causes the splitting into an equal intensity triplet; however, hyperfine anisotropy may contribute to the dominant effect for observing line shape of organic radical at X-band frequencies in the solid state. 22 In particular, the electron Zeeman interaction (H EZ ) is occurred between the unpaired electron and the magnetic field. 23 While the electron-nuclear hyperfine interaction (H HF ) is between unpaired electron ( S = 1/2) and 14 N nucleus ( I = 1) of the nitroxide group (N–O˙).…”
mentioning
confidence: 99%